Integrated Nutrient Management and Intercropping in Increasing the Productivity of Curly Chili (Capsicum Annum L) - Alwan, Nur Ibnu; Nihayati, Ellis; Maghfoer, Moch Dawam (Agro Bali : Agricultural Journal, 2024)
Curly chili (Capsicum annum L.) is one horticultural commodity with good development prospects. The productivity of chili plants in Indonesia is quite low. The cause is low land productivity due to intensive planting and excessive use of inorganic fertilizers. One way to overcome this problem is by combining inorganic and organic fertilizers. This research aims to obtain the proportions of various nutrient sources and types of intercropping that can increase the production of curly red chili plants. This research was conducted in June – December 2021 in Wonorejo Village, Poncokusumo District, Malang Regency. This research used a Randomized Block Design (RBD). (P0) chili monoculture (P1) chili + pakchoy (P2) chili + cabbage (F0) 100% inorganic (F1) 75% N + 20 t goat manure + PGPR 10 ml 1-1 (F2) 75% N + 20 t goat manure + PGPR 20 ml 1-1 (F3) 50% N + 30 t goat manure + PGPR 20 ml 1-1. The results showed that the P1F2 treatment: chili + pakcoy, 75% N + 20 t goat manure + PGPR 20 ml 1 showed high growth results, namely plant height, number of leaves and stem diameter, and the highest yield component per hectare, namely 8.6 tons/ha.